A comparision of efficacy of risperidone and olanzapine in schizophrenia patients - Shah, SK; Ojha, SP; Koirala, NR; Sharma, VD; Yengkokpam, B (Journal of College of Medical Sciences-Nepal, 2012)
Schizophrenia is a leading worldwide mental health problem. It is also one of the common and challenging problems in Nepal. Risperidone and olanzapine is one of the major antipsychotic drug used for schizophrenia patients, however their efficacy is not compared in Nepal.To assess the efficacy of risperidone and olanzapine in schizophrenia patients in Nepalese context. An open-label, randomized, comparative, prospective study was done for 6 weeks. Total of 63 patients attending Psychiatry OPD in Jan to July 2008 at TUTH who could be available for close follow up were enrolled with consent. Risperidone was given in dose of 3-6 mg and Olanzapine in the dose of 15-20 mg per day. Efficacy and tolerability was assessed using PANSS, CGI, and UKU side-effect checklist. Both groups showed improvement in the entire positive, negative and general psychopathology subscales without significant difference in the two groups. Regarding tolerability, olanzapine was found to have significant sedation, weight gain while with risperidone extrapyramidal side-effects, palpitations, sexual side-effects were significant. Risperidone and olanzapine both are efficacious in the treatment of schizophrenia. Both the drugs have their own side-effects. Long-term efficacy and tolerability needs to be studied. As it has been seen in the ongoing studies, long-term use and side-effect profile, drop-out rates and the increase in metabolic syndromes need more consideration. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6706 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 29-35